A study of accident investigation methodologies applied to the Natech events during the 2011 Great East Japan earthquake. (January 2018) - Chakraborty, Anirban; Ibrahim, Ahmed; Cruz, Ana Maria
Abstract: Na tural hazard triggeredtech nological (Natech) events are low probability but high impact events. It is a relatively new challenge faced by the people involved in disaster risk management and can be particularly complicated. Their rarity signifies the importance to study and analyze past events. The lessons learnt from those accident investigations should be adopted while preparing for possible future occurrences. Accident investigation methods help to better understand the course of events and the causes leading to them. The Department of Energy in the United States and the Centre for Chemical Process Safety, amongst others, list and describe various analytical approaches. Still, in the field of Natech accident investigation these methods are yet to take the commonplace. There is a problem of many available methods and a lack of appropriate literature assessing their ease of usage and applicability so that relevant methods can be selected to address a particular Natech accident. The present study is part of an initiative started at the Joint Research Centre of the European Commission to evaluate various accident investigation methods in order to help SEVESO sites and competent authorities in the selection of analytical approaches and extraction of the lessons learned. In this paper, some selected accident investigation methods are applied to two Natech accidents in Japan on the aftermath of the 2011 Great East Japan earthquake along with an evaluation of the accident investigation methods with regards to the depth of the investigation results, ease of usage, applicability etc. The evaluation results established that not one method can satisfactorily analyze an accident as complex as a Natech event and thus, a general approach to select the investigation methods is also discussed. Highlights: Two different Natech accident case studies during 2011 Great East Japan Earthquake are investigated. DOE, CCPS approved accident investigation methods are applied for systematic analysis. Safety problems are identified from the individual case studies based on the analysis. The investigation methods are then evaluated considering the depth of the results, ease of usage, applicability etc. A general approach to select the investigation methods for a Natech accident is also discussed.